Encephalitozoon cuniculi Genotype II Concentrates in Inflammation Foci - Brdíčková, Klára; Sak, Bohumil; Holubová, Nikola; Květoňová, Dana; Hlásková, Lenka; Kicia, Marta; Kopacz, Żaneta; Kváč, Martin (Journal of inflammation research, 2020)
BACKGROUND: Microsporidia of the genus Encephalitozoon are generally connected with severe infections with lethal outcome in immunodeficient hosts. In immunocompetent hosts, microsporidiosis typically establishes a balanced host-parasite relationship that produces minimal clinically overt disease. Although the alimentary tract represents one of the main primary target tissues, the mechanisms of reaching other tissues during systemic microsporidian infections remain unclear. METHODS: In the present study, we tested the relation between inflammation induction in immunocompetent and immunodeficient mice and the presence of spores of E. cuniculi genotype II in selected organs and in fecal specimens by using molecular and histology methods. RESULTS: We reported the positive connection between inflammation induction and the significant increase of E. cuniculi genotype II occurrence in inflammation foci in both immunocompetent BALB/c and immunodeficient severe combined immunodeficient (SCID) mice in the acute phase of infection and the re-activation of latent microsporidial infection following inflammation induction in immunocompetent mice. CONCLUSION: The results imply possible involvement of immune cells serving as vehicles transporting E. cuniculi genotype II purposefully across the whole host body towards inflammation. With increasing number of records of infections, it is necessary to reconsider microsporidia as agents responsible for various pathologies. The elucidation of possible connection with pro-inflammatory immune responses represents an important challenge with consequences for human health and development of therapeutic strategies.
Keywords: targeted migration; Encephalitozoon cuniculi; inflammation